The Influence of Innovation Models, Micro Small and Medium Enterprises, and Development Strategies Towards Cooperatives in Industrial Era 4.0 - Arjuna Rizaldi; Ecie Linasari (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2021)
Cooperatives are Business entities that are driven and owned by members seeking to achieve common needs in various fields, utilizing the Industrial Era 4.0 in order to reach its goals. This paper aims to point out the impacts of innovation models, micro small and medium enterprises, and development strategies towards cooperatives in industrial era 4.0. Research methods outlined that are applied in this paper consists of Qualitative, Quantitative, Descriptive, and secondary research approaches. The results regarding to this paper are as follows. With the innovation model designated for the cooperative’s renovation, it is expected that it has a positive impact on cooperatives and its pupils, creating a healthy and fair transaction process. Furthermore, small, medium and micro businesses as well as cooperatives need to adopt survival strategies and strategic methods, apply modern systems to their business processes, and strive to successfully answer various global challenges in the era of the Industrial Revolution 4.0. Finally, the transformation of the cooperative development strategy needs to be carried out considering that the new challenges of cooperatives are not only related to how to do business in the digital era but also change the overall perspective of the governance found in a cooperative of this modern era.